Application of one- And two-ended impedance based fault location algorithms for distance protection - Wolf, Michael; Prommetta, Jonas; Jäger, Johann (PESS 2020 - IEEE Power and Energy Student Summit, Conference Proceedings, 2020)
In this paper the use of communication based fault locating algorithms for distance protection is discussed. The goal is to compensate various error sources regarding the reactance measurement i.e. the fault location. First, state-of-the-art distance protection algorithms and their problems in fault locating are presented. After identifying prefault loadflow and network inhomogeneity combined with a fault resistance as the main sources for measurement errors, methods are presented that are able to compensate these error sources. The algorithms are validated on a Simulink model of a double side supplied line. The results indicate that by using the communication based algorithms the determination of the fault location can be improved as their calculation method is independent of prefault loadflow and network inhomogeneity, whereas the state-of-the-art methods display significant inaccuracies.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Communication based fault locating algorithms; Distance protection algorithm; Reactance method